PENGEMBANGAN POCKETBOOK PEMBELAJARAN MUFRADÂT BERBASIS ANTI RADIKALISME BAGI MAHASISWA JURUSAN PENDIDIKAN BAHASA ARAB - Ali, Jauhar (Universitas Negeri Semarang, 2021)
This research aims to find out and describe the development of pocketbooks for Arabic vocabulary learning (mufradât) based on anti-radicalism for students majoring in Arabic Language Education (PBA) FTIK IAIN Pekalongan. This study's results are expected to make a real contribution to the advancement or development of Arabic vocabulary learning media (mufradât) based on anti-radicalism and add scientific insight into the development of Arabic vocabulary learning media (mufradât) based on anti-radicalism. This development research uses analysis, design, development, implementation, and evaluation (ADDIE) models. The results showed: (1) The resulting product form in the form of pocketbook Arabic vocabulary (mufradât) based on anti-radicalism size 11 cm x 15cm with a total of 61 pages. The first section contains an introduction (foreword and table of contents), the second part of the material's content, the Arabic vocabulary (mufradât) based on anti-radicalism, and the last page a list of libraries. This book is made practically and interestingly to make it easier for users and not dull for students. This pocketbook media can be reproduced easily so that every student can have it personally; (2) Based on the assessment of experts, it can be concluded that this pocketbook medium is worthy of use in Arabic vocabulary (mufradât). The material expert rated the results 71 in the category of